Determinants of Foreign Direct Investment in Malaysia / Nur Syamihah Abdul Ghani - Abdul Ghani, Nur Syamihah (2015)
This paper studies the determinants of foreign direct investment in Malaysia. The primary focus on this study is to determine the relationship between independent variables which consist of exchange rate, infrastructural development and inflation rate with the dependant variable, FDI. The objective is to develop a regression equation between the economic variable namely exchange rate, infrastructural development and inflation rate with dependent variable FDI. For the data collected is sample that is used base on 8 years quarterly data of exchange rate, infrastructural development and inflation rate starting from 2007 until 2014. The analysis is made by using statistical software Eviews in order to analyse all the related data and interpret the result findings. The study revealed that, all variables have significantly relationship with FDI